Reputasi KAP dalam Memoderasi Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas dan Likuiditas Terhadap Audit Report Lag - Ma’sumah, Lulu’il; Rusyida, Wilda Yulia (IAIN Kudus, 2022)
This research was conducted to determine the effect of company size, profitability, solvency, and liquidity on audit report lag with the reputation of public accounting firms as a moderating variable in state-owned companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This type of research is quantitative research. The data used secondary data using purposive sampling. This study conducted descriptive analysis tests, classical assumption tests, and hypothesis tests consisting of the coefficient of determination, t-test, and Moderated Regression Analysis (MRA). The results of this study show that company size, profitability, and liquidity affect the audit report lag companies. In contrast, solvency has no effect. The reputation of the public accounting firm cannot moderate the relationship between firm size, profitability, solvency, and liquidity in the audit report.